Adverse effects of golimumab in the treatment of rheumatologic diseases. (January 2014) - Yang, Hong; Kavanaugh, Arthur
<x xml:space="preserve">Abstract</x> Introduction: A number of new biological immune modulators have become available as treatments for inflammatory diseases over the past two decades. Most prominent among them are TNF-α inhibitors (TNFi) which have been available in the clinic since the late 1990s. TNFi have demonstrated efficacy in various rheumatologic diseases as well as in inflammatory bowel disease and psoriasis. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Golimumab&logicalOpe1=OR&field2=articletitle&text2=Golimumab&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Golimumab is one of the most recently introduced TNFi. Areas covered: Although golimumab is generally well tolerated, as is the case with other TNFi and indeed with most of the marketed immunomodulatory drugs, potential adverse events may be associated with its use. Herein, we the potential adverse effects associated with golimumab therapy are reviewed. Adverse effects are divided into target-related and agent-related categories. Expert opinion: Golimumab has been demonstrated to be generally safe and well tolerated. Its safety profile seems to be very comparable to the other available TNFi. Long-term studies of golimumab and other TNFi will help establish the durability of response to golimumab as well as identify any potential delayed or cumulative adverse effects.